Hypertrophic Cardiomyopathy as a cause of Sudden Cardiac Death—An Autopsy Study - Kanwardeep Kaur Tiwana, Manmeet Kaur2 , Mohanvir Kaur3, Shaffaly Gagneja4 , Haspreet Kaur5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Sudden cardiac death (SCD) is an unexpected death with underlying cardiac pathology. Hypertrophiccardiomyopathy is one of the causes of SCD. It comes almost second important cause after Ischemic pathology.However, it remains to be explored. It is a 10-year retrospective study done between (2002-2020) includingall the postmortem cases of SCD coming to the Department of Pathology for histopathological examination.The present study highlights various histopathological features of hypertrophic cardiomyopathy